1994
DOI: 10.1111/j.1432-1033.1994.tb18574.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of the interaction between salivary proline‐rich proteins and a polyphenol by 1H‐NMR spectroscopy

Abstract: The interaction between salivary proline-rich proteins and plant polyphenols (tannins) in the oral cavity and their subsequent precipitation influences the taste, texture and nutritional value of food ; it is thought to be responsible for the astringency of many foods and beverages. To investigate the interaction, two-dimensional 'H-NMR studies have been carried out on the binding of a representative polyphenol, pentagalloyl glucose, to two synthetic peptides (19 and 22 residues in length) that are typical of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
148
2
3

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(164 citation statements)
references
References 18 publications
11
148
2
3
Order By: Relevance
“…It was also suggested that the unique characteristics of the Pro residue, its flat and rigid structure and hydrophobicity, is important in the tannin-protein interactions at the bturn structure and not only in linear peptides. 1,2) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also suggested that the unique characteristics of the Pro residue, its flat and rigid structure and hydrophobicity, is important in the tannin-protein interactions at the bturn structure and not only in linear peptides. 1,2) …”
Section: Resultsmentioning
confidence: 99%
“…Recently, the preferential association of tannins with proline (Pro) residues in linear peptides was reported. 1,2) Pro residues disrupt both a-helix and b sheet conformation in the peptide secondary structure and commonly occurs on the surfaces of proteins. 3) Since Pro residues are frequently found near protein-protein interaction sites, 4) the preferential interaction of tannins with Pro residues may be related to the broad biological activities of tannins including enzyme inhibition.…”
mentioning
confidence: 99%
“…The upfield changes in chemical shift seen on titration of the protein with tannins can be ascribed to ring current shifts, caused largely by face-to-face stacking of the prolyl rings of the protein with the galloyl rings of the tannins [5]. Each proton within the protein experiences different upfield shifts due to local tannin binding, and therefore the curve fitting procedure essentially yields individual microscopic dissociation constants for each site in the protein.…”
Section: Discussionmentioning
confidence: 99%
“…where ASi is the change in chemical shift, [P]i is the total concentration of protein, [T]i is the total concentration of polyphenol, [P] This expression assumes a 1:1 binding interaction at each fitted proton, which has been justified elsewhere for PRP/polyphenol ass()-ciations [5]. The curve fittings were performed using EXCEL (Microsoft Corp.).…”
Section: T T R L I J) R J J > Jmentioning
confidence: 99%
See 1 more Smart Citation